(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Tuberculosis (TB) remains one of the leading infectious causes of morbidity and mortality worldwide. Concurrently, the global prevalence of diabetes mellitus (DM) continues to rise, creating a significant challenge for healthcare systems. Diabetes mellitus is recognized as an important risk factor for the development, progression, and unfavorable outcomes of pulmonary tuberculosis. The coexistence of these two diseases alters the clinical presentation, radiological manifestations, immune response, and treatment outcomes. Hyperglycemia impairs both innate and adaptive immunity, increasing susceptibility to Mycobacterium tuberculosis infection and reactivation of latent tuberculosis. Patients with diabetes frequently demonstrate more extensive pulmonary lesions, delayed sputum conversion, increased bacterial load, and higher rates of treatment failure and relapse. This review summarizes current evidence regarding the peculiarities of pulmonary tuberculosis in patients with diabetes mellitus, including epidemiological trends, pathogenetic mechanisms, clinical manifestations, diagnostic challenges, and therapeutic considerations.